GAMBARAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Riki Musriandi; Saifuddin Saifuddin; Ruwaida Ruwaida (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to determine students' mathematical problem solving abilities. The form of research used in this research is quantitative descriptive research. This research was conducted on students VIII MTsN Kuta Baro Aceh Besar. The sample used is students VIII-1 and VIII-2 by using purporsive sampling techniques. The instrument used is a matter of form of test description that has been validated. The data analyzed is the students' answers to the questions given. The results of the study obtained that the mathematical problem solving ability of students of class VIII MTsN Kuta Baro who were already good as much as 49% or equal to 21 people, enough 46% or equivalent to 20 people and in the category of less than 5% or equivalent to 2 people. From these results, the mathematical problem solving ability of students of class VIII MTsN Kuta Baro still needs to be the attention of the teacher in order to improve the mathematical solving abilities of students of class VIII MTsN Kuta Baro.